Análise do impacto no desempenho econômico e financeiro de empresas do varejo listadas na B3 durante a pandemia de Covid 19 no ano de 2020 - Diehl, Jonas (2021)
The present study consists of demontrate, after the review and analysis indicators of the financial statements, the economic and financial performance compared of three companies of the retail sector and listed by B3, brazilian stock excchange. The paper discusses the importance of knowing the scenario in which the company finds itself, e the necessity of the correct analysis and correct interpretation of the informations contained in the financial statements, to assist in organizational management and ensure that assertive decisions are taken. The research method used in this paper is the quantitative, with a descriptive objective. The research target population are the companies Magazine Luiza, Lojas Americanas and Via Varejo. The sampling is non-probabilistic. The data collection procedure used in the study is characterized by the use of secondary data. The study is based on indicators drawn from the Balance Sheet and Income Statement for the year available on the B3 website. The external environment affected the results of organizations around the world in 2020 due to the Covid-19 pandemic, including the companies whose data is being analyzed. The informations obtained by research demonstrates positive and negative points in the three companies and highlights the differences in performance in the years object of the analysis. The results presented reveal that the three companies had an increase by internet sales. Magazine Luiza obtened the best growth in sales and inventory turnover. Lojas Americanas presented the best liquidity indexes and the best average payment term and sales receivables. Via Varejo had a better evolution in gross profit and adjusted costs and expenses, resulting in a higher net profit compared to the other companies analyzed in the second year whose data were analyzed. All three companies presented high indebtedness index